2015
DOI: 10.1186/s13395-015-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin as a mediator of sarcopenia versus homeostatic regulator of muscle mass: insights using a new mass spectrometry-based assay

Abstract: BackgroundMyostatin is a protein synthesized and secreted by skeletal muscle that negatively regulates muscle mass. The extent to which circulating myostatin levels change in the context of aging is controversial, largely due to methodological barriers.MethodsWe developed a specific and sensitive liquid chromatography with tandem mass spectrometry (LC-MS/MS) assay to measure concentrations of myostatin and two of its key inhibitors, follistatin-related gene (FLRG) protein and growth and serum protein-1 (GASP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
109
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 42 publications
13
109
1
2
Order By: Relevance
“…Along the same lines, in some studies, muscle mass was inversely correlated with serum myostatin levels [11]. However, more recent studies have shown a positive correlation between lean mass or muscle strength and myostatin [10, 12]. …”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Along the same lines, in some studies, muscle mass was inversely correlated with serum myostatin levels [11]. However, more recent studies have shown a positive correlation between lean mass or muscle strength and myostatin [10, 12]. …”
Section: Introductionmentioning
confidence: 80%
“…Accordingly, relative muscle mass was inversely correlated with serum myostatin [11]. However, other studies reported that the concentration of myostatin decreases with age in men [12, 13]. Few studies have analyzed the interaction between frailty indexes and serum myostatin levels; some found higher levels of myostatin in physically frail women than in their non-frail counterparts [11, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle mass is regulated by myostatin, a member of the transforming growth factor‐β superfamily and a potent negative regulator of muscle growth 6, 7, 8. Myostatin is upregulated in obesity and downregulated by exercise 9, 10, 11, 12. Targeted inhibition of myostatin, genetically or pharmaceutically, has had promising results in improving cardiometabolic health (namely, glucose tolerance) and preventing/restoring muscle mass in rodents and humans 8, 13, 14, 15, 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…Circulating sclerostin appears to correlate with total body bone mass (i.e., the number of osteocytes), and levels are higher in men than in women [5]. Furthermore, several studies show a poor correlation between circulating sclerostin versus expression in bone [6]. Thus, one explanation for higher myostatin levels in fitter, less frail individuals might be its known (although moderate) correlation with total muscle mass [7].…”
mentioning
confidence: 99%